The influence of emotional intelligence on deviant behavior with intention to move as a mediating variable - Ninda Reflisia; Syahrizal Syahrizal (Universitas Negeri Padang, 2021)
The purpose of this study was to analyze the influence of emotional intelligence on deviant behaviors through turnover intention as a mediator of at the Rangkayo Basa Padang Hotel. This research belongs to the type of causative descriptive research. The population in this study were all employees in the Rangkayo Basa Padang Hotel. The sampling technique in this study used a total sampling technique which amounted to 90 people. The analysis technique used is SEM analysis using PLS3 smart. The results of this study indicate that: (1) Emotional Intelligence has a negative and significant effect on deviant behaviors employees of Rangkayo Basa Padang Hotel. (2) Negative and significant emotional intelligence on employees turnover intention of Rangkayo Basa Padang Hotel. (3) Positive and significant turnover intention on the deviant behaviors on employees of Rangkayo Basa Padang Hotel. (4) Emotional intelligence is to be significant towards the deviant behavior employees of Rangkayo Basa Padang Hotel with turnover intention as a mediating variable.